Evaluation of seed yield of durum wheat (Triticum durum) under drought stress and determining correlation among some yield components using path coefficient analysis (UNED Research Journal, 2018)
Water deficit affects can have negative effects on grain formation. I investigated the relationships between the characters of durum wheat (Triticum durum) and yield under drought stress and identified the most effective components of yield. I used 49 durum wheat genotypes (43 exotic and 6 local lines), in a lattice design (7×7) replicated twice, during tillering, stem elongation, anthesis and grain filling. There were positive correlations among harvest index (r=0,849), plant height (r=0,695), tillering (r=0,689), peduncle length (r=0,466) and grain yield. The number of seeds per spike (0,432), spike length (0,410) and 1 000 seed weight (0,385) had the highest direct effect on yield.
Keywords: Correlation; drought stress; durum wheat; Triticum; path analysis